Empathy and inclusivity to people from different cultures - Abdul Razak, Mohd Abbas; Hanif, Syed Sikandar Shah; Abdurrahman, Muhammad AR (2020)
The day men came to exist on this planet they became conscious of their differences when compared to others. Things like colour, language, dialect, ethnicity, tribe, religion, religious denomination, country of origin, culture, tradition, etc. can be factors that divide humanity. At times, such division can cause hatred, discrimination, racism and perhaps cause nations to go into war against one another. On the contrary, qualities like feeling empathy and inclusivity can make an individual to be thoughtful and sensitive towards one another. Through this webinar session with the students of COMM 3090 IIUM, we were able to communicate some Islamic ideas to the students and general audience. Ideas from the team were communicated via the Cyberworld. The findings indicated that schools, students, learning institutions, governments, nations around the globe, plus the United Nations should campaign against racism, marginalization of minorities, sectarian violence, foreign occupation, war, etc. in order to create a better world where peace and harmony prevail and people can live in acceptance of one another.